2002
DOI: 10.1016/s0925-8388(02)00435-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sorption properties of the nanocomposites Mg–Mg2Ni1−xFex

Abstract: The hydrogen sorption properties of the composites 85 wt.% Mg-15 wt.% Mg Ni Fe (x50, 0.1 and 0.3) prepared by high-energy 2 12x x ball milling were studied. It was shown that the presence of a Mg Ni Fe additive significantly improved the kinetics of hydrogen 2 12x x absorption and desorption of magnesium, the absorption capacity remaining sufficiently high even at temperatures between 423 and 573 K. The catalytic effect of the Mg Ni Fe intermetallics was explained as due to the formation of a second hydride, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Finally, in CeNi all Ce-Ni distances are equal to 2.97 Å while in CeNiH 2.9(1) the hydrogen occupancy induces an anisotropic change, as a result of which each Ni atom is surrounded by 4 cerium atoms at a distance of 3.15 Å (in the a-c plane) and 2 cerium atoms at 3.37 Å (in the b direction). This change in the Ni environment proves that the hydrogen atoms are located in the [Ce 3 Ni] tetrahedra as was to be expected on the basis of the parameter changes. Moreover, for the isostructural ZrNi compound, the hydrogenation also induce a huge increase of the volume cell (i.e.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Finally, in CeNi all Ce-Ni distances are equal to 2.97 Å while in CeNiH 2.9(1) the hydrogen occupancy induces an anisotropic change, as a result of which each Ni atom is surrounded by 4 cerium atoms at a distance of 3.15 Å (in the a-c plane) and 2 cerium atoms at 3.37 Å (in the b direction). This change in the Ni environment proves that the hydrogen atoms are located in the [Ce 3 Ni] tetrahedra as was to be expected on the basis of the parameter changes. Moreover, for the isostructural ZrNi compound, the hydrogenation also induce a huge increase of the volume cell (i.e.…”
Section: Resultssupporting
confidence: 72%
“…No reaction between the components of the composite was observed during its preparation by mechanical grinding but it was shown that the presence of YNi led to an improvement of magnesium hydriding kinetics even at relatively low temperatures. The X-ray diffraction patterns of the products obtained at 300 8C after several hydriding-dehydriding cycles showed formation of MgH 2 , Mg 2 NiH 4 , YH 2 and YNiH 3 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These two preparation methods have been applied in the present work to the Mg-Ni-Fe system, which results interesting on the basis of previous studies [5]. Samples obtained by short time ball milling Mg-Ni-Fe melt spun ribbons have been compared to samples obtained by long time ball milling a MgH 2 , Ni and Fe powder mixture.…”
Section: Introductionmentioning
confidence: 74%
“…In this system, palladium serves two purposes: It acts as a protecting layer to prevent surface passivation of the Mg/MgH 2 film and as a catalyst for hydrogen dissociation and the resultant spillover. 33 The embedded iron is thought to act as a secondary metal catalyst to facilitate the 34 The enhanced desorption kinetics of the composite were attributed to a new hydride phase forming from the ternary intermetallic dopant.…”
Section: Bimetallic Structuresmentioning
confidence: 99%